2007
DOI: 10.1016/j.bpc.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Destabilised mutants of ubiquitin gain equal stability in crowded solutions

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A C C E P T E D M A N U S C R I P T ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
(117 reference statements)
6
18
1
Order By: Relevance
“…This result suggests, as previously proposed, that the effect of macromolecular crowding on protein folding stability can be modeled by confinement of the protein of interest to a spherical cavity. 23 However, in contrast to theoretical prediction, but in agreement with other experimental studies, 11,14,21 we found that the stabilization arising from crowding shows a weak, if any, dependence on the size of the crowding agents used in the current study. Taken together, these findings suggest that the microscopic compartmentalization of these polymer solutions is different from what is expected based on the hydrodynamic radii of the crowders and underscore the need for further improvement of existing crowding theories.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This result suggests, as previously proposed, that the effect of macromolecular crowding on protein folding stability can be modeled by confinement of the protein of interest to a spherical cavity. 23 However, in contrast to theoretical prediction, but in agreement with other experimental studies, 11,14,21 we found that the stabilization arising from crowding shows a weak, if any, dependence on the size of the crowding agents used in the current study. Taken together, these findings suggest that the microscopic compartmentalization of these polymer solutions is different from what is expected based on the hydrodynamic radii of the crowders and underscore the need for further improvement of existing crowding theories.…”
Section: Discussioncontrasting
confidence: 57%
“…Such a stark difference between theoretical prediction and experiment cannot be attributed to experimental uncertainty, but must arise from other reasons. Similarly, other experimental studies have also found either no 11 or a weak 14,21 dependence of the thermal stability of proteins on the crowder size. The origin of the observed discrepancy may be because when mapping a given crowded solution onto a spherical cavity via R = (4π/3ϕ) 1/3 R c , void formation due to density fluctuations in the crowded solution is not taken into account.…”
Section: Dependence Of T M On Crowder Size and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Many experimental studies have been directed at measuring how much crowding agents affect the folding, conformational transition, and binding equilibria (Qu and Bolen 2002; Spencer et al 2005; Roberts and Jackson 2007; Batra et al 2009a; Batra et al 2009b; Phillip et al 2009; Dhar et al 2010; Miklos et al 2011; Denos et al 2012), often spurred by Minton’s predictions of significant crowder-induced stabilization of the compact states over the more open states (Minton 1981, 1998, 2000, 2005). The predictions are largely based on the scaled particle theory (Lebowitz and Rowlinson 1964) for the free energy of transferring a test protein into crowders, all of which are modeled as convex hard particles.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by these authors that the conformational distortions around residue 45 are minimal and that the 3D structure is very close to the wt. Other authors [17] denoted this mutant as a pseudo wild type wt*. However, according to Roder and coworkers an enhanced flexibility exists in the region of amino acids 45-48.…”
Section: Strategy For Mutationmentioning
confidence: 95%